Outcomes of Patients Lost to Follow-up in African Antiretroviral Therapy Programs: Individual Patient Data Meta-analysis. (8th June 2018) - Chammartin, Frédérique; Zürcher, Kathrin; Keiser, Olivia; Weigel, Ralf; Chu, Kathryn; Kiragga, Agnes N; Ardura-Garcia, Cristina; Anderegg, Nanina; Laurent, Christian; Cornell, Morna; Tweya, Hannock; Haas, Andreas D; et al.
Abstract : Retention on antiretrovirals is of concern in Africa. We analyzed outcomes in patients lost to follow-up: at 4 years after last contact, 22% had died, 23% had stopped therapy, 15% were in another clinic, and 32% could not be found. Abstract: Background: Low retention on combination antiretroviral therapy (cART) has emerged as a threat to the Joint United Nations Programme on human immunodeficiency virus (HIV)/AIDS (UNAIDS) 90-90-90 targets. We examined outcomes of patients who started cART but were subsequently lost to follow-up (LTFU) in African treatment programs. Methods: This was a systematic review and individual patient data meta-analysis of studies that traced patients who were LTFU. Outcomes were analyzed using cumulative incidence functions and proportional hazards models for the competing risks of ( i ) death, ( ii ) alive but stopped cART, ( iii ) silent transfer to other clinics, and ( iv ) retention on cART. Results: Nine studies contributed data on 7377 patients who started cART and were subsequently LTFU in sub-Saharan Africa. The median CD4 count at the start of cART was 129 cells/μL. At 4 years after the last clinic visit, 21.8% (95% confidence interval [CI], 20.8%–22.7%) were known to have died, 22.6% (95% CI, 21.6%–23.6%) were alive but had stopped cART, 14.8% (95% CI, 14.0%–15.6%) had transferred to another clinic, 9.2% (95% CI, 8.5%–9.8%) were retained on cART, and 31.6% (95% CI, 30.6%–32.7%) could not been found. Mortality was associated with male sex, more advanced disease, and shorter cART duration; stopping cART with less advanced disease andlonger cART duration; and silent transfer with female sex and less advanced disease. Conclusions: Mortality in patients LTFU must be considered for unbiased assessments of program outcomes and UNAIDS targets in sub-Saharan Africa. Immediate start of cART and early tracing of patients LTFU should be priorities.